Convergence between Artificial Intelligence and Audiovisual Production:: A Bibliometric Analysis of its Evolution, Trends and Contributions (2000-2024) - Cruz Oña, Ariel Omar; Andrade Sánchez , Edison David (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Over the past 25 years, the convergence between artificial intelligence (AI) and audiovisual production has driven disruptive advancements with interdisciplinary impact. This study presents a comprehensive bibliometric analysis using the Bibliometrix tool in R Studio to examine the evolution of research in this field. Emerging trends, interinstitutional collaboration networks, and the geographical distribution of knowledge production are identified. In addition, the most influential authors, institutions, and countries leading scientific development are highlighted, emphasizing the relevance of interdisciplinary cooperation. The findings reveal the transformation of the field and pinpoint areas with high potential for future research. This contribution aims to guide new lines of inquiry and support the formulation of scientific and technological policies.